Hydrocarbon accumulation conditions and models in fault -depression superimposed basin: a case in Longfengshan area in Songliao basin, China. Issue 2 (July 2021) - Fan, Jie; Jiang, Youlu; Zhang, Kuihua; Zeng, Zhiping; Gong, Yajun; Gao, Jianxiong; Zhu, Jianfeng
Abstract: Songliao Basin develops typical fault-depression superimposition dual structure in vertical. So far, the depression sequence has achieved continuous stable yield of oil and gas, while it is of great significance to deepening exploration of hydrocarbon in faulted sequence. Taking the new Longfengshan Area as the research object, in light of the analysis of source rock condition, source of hydrocarbon, passage system, caprock condition and accumulation period, the dynamic hydrocarbon accumulation process is recovered, and hydrocarbon accumulation models are established. Research shows that K1sh Formation source rock in the northern depression zone has good hydrocarbon generation capacity, which provides high quality source condition. What is more, effective configuration between sealing faults and connected sandstone provides important hydrocarbon migration and accumulation condition. Meanwhile, the top of K1yc3 Formation mudstone caprock has good fault-caprock configuration, which provides good hydrocarbon preservation condition. The hydrocarbon accumulation model of study area can be summarized as "source rock in sag zone supplies hydrocarbon, fault-sandstone configuration controls hydrocarbon migration, faults-caprocks configuration controls hydrocarbon accumulation" pattern which embodies the characteristics of "rapid vertical transporting by faults, fault-sandbody configuration, caprocks control hydrocarbon accumulation" in the stage of fault-depression transition and "sealing by faults, sandstone conducts laterally- faults, caprocks control hydrocarbon accumulation" in the stage of depression.